Fractional Calculus of a Unified Mittag-Leffler Function - Nathwani, B. V.; Prajapati, J. C. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
The main aim of the paper is to introduce an operator in the space of Lebesgue measurable real or complex functions L(a, b). Some properties of the Riemann–Liouville fractional integrals and differential operators associated with the function E α,β,λ,μ,ρ,p γ,δ (cz; s, r) are studied and the integral representations are obtained. Some properties of a special case of this function are also studied by the means of fractional calculus.